2007
DOI: 10.1080/13607860601086504
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Piano Instruction enhances executive functioning and working memory in older adults

Abstract: This study evaluates transfer from domain-specific, sensorimotor training to cognitive abilities associated with executive function. We examined Individualized Piano Instruction (IPI) as a potential cognitive intervention to mitigate normal age-related cognitive decline in older adults. Thirty-one musically naïve community-dwelling older adults (ages 60-85) were randomly assigned to either the experimental group (n = 16) or control group (n = 15). Neuropsychological assessments were administered at three time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
308
4
23

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(357 citation statements)
references
References 36 publications
22
308
4
23
Order By: Relevance
“…In individual trials we found that mental stimulation groups significantly outperformed "no intervention" controls on four out of eight memory measures (Carlson et al, 2008;Klusmann et al, 2010;Noice and Noice, 2009;Slegers et al, 2009), nine out of 17 measures of executive function (Basak et al, 2008;Bugos et al, 2007;Carlson et al, 2008;Klusmann et al, 2010;Noice and Noice, 2009;Slegers et al, 2009;Tesky et al, 2011), and one out of three composite measures of cognitive function (Slegers et al, 2009;Tesky et al, 2011;Tranter and Koutstaal, 2008). The trials did not include measures of everyday functioning.…”
Section: Mental Stimulation Versus 'No Intervention'mentioning
confidence: 87%
See 1 more Smart Citation
“…In individual trials we found that mental stimulation groups significantly outperformed "no intervention" controls on four out of eight memory measures (Carlson et al, 2008;Klusmann et al, 2010;Noice and Noice, 2009;Slegers et al, 2009), nine out of 17 measures of executive function (Basak et al, 2008;Bugos et al, 2007;Carlson et al, 2008;Klusmann et al, 2010;Noice and Noice, 2009;Slegers et al, 2009;Tesky et al, 2011), and one out of three composite measures of cognitive function (Slegers et al, 2009;Tesky et al, 2011;Tranter and Koutstaal, 2008). The trials did not include measures of everyday functioning.…”
Section: Mental Stimulation Versus 'No Intervention'mentioning
confidence: 87%
“…Each of the mental stimulation interventions resulted in a transfer of effects to at least one cognitive outcome measure (table 3). Neither trial that included follow-up assessments reported maintenance of intervention effects (Bugos et al, 2007;Slegers et al, 2009). …”
Section: Mental Stimulation Versus 'No Intervention'mentioning
confidence: 99%
“…For example, music is most often played in coordination with others (Palmer, 2013), which requires switching between multiple auditory streams (Loehr, Kourtis, Vesper, Sebanz, & Knoblich, 2013) and adjusting to other performers (e.g., Loehr & Palmer, 2011;Moore & Chen, 2010). Thus music performance may be associated with relatively general switching advantages, and musicians have indeed been found to outperform non-musicians on switching tasks (Hanna-Pladdy & MacKay, 2011;Moradzadeh, Blumenthal, & Wiseheart, 2014; see also Bugos, Perlstein, McCrae, Brophy, & Bedenbaugh, 2007;Zuk, Benjamin, Kenyon, & Gaab, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A través del piano y aplicándolo a personas mayores de entre 60 y 85 años, Bugos et al (2007) mostraron que este instrumento musical puede servir para una intervención cognitiva eficaz relacionada con la edad y el deterioro cognitivo. También estos autores asocian el ejercicio aeróbico con un deterioro cognitivo más lento, aunque el objetivo de su investigación fue el de prevenir o mantener habilidades cognitivas desde la música, además de prevenir la pérdida de memoria desde el aprendizaje del piano.…”
Section: Otra Estrategia: Euritmiaunclassified